Quality changes kinetics of apple tissue during frozen storage with temperature fluctuations. (August 2018) - Vicent, V.; Ndoye, F.T.; Verboven, P.; Nicolaï, B.M.; Alvarez, G.
Highlights: Quality changes in apple tissue were studied during frozen storage. Temperature fluctuations significantly affect the apple quality during storage. The quality data were fitted to first order kinetics. A developed kinetic model can be used to predict the apple quality evolution. Abstract: Apple quality after freezing is affected by temperature fluctuations during cold storage. Ice re-crystallization and sublimation occur slowly at a constant temperature over a long period of storage, and more rapidly during fluctuating temperatures. These phenomena impact fruit quality, thus reducing storage life. To this end, apple tissue samples were frozen and subsequently stored in three different freezers set at −12 ± 3 °C, −18 ± 3 °C, and −23 ± 3°C. In each freezer, three different compartments were created to achieve different amplitudes of temperature fluctuations: (i) low (± 0.1 °C), (ii) medium (± 0.5 °C) and (iii) large (± 1.8 °C). Frost formation, drip loss, color changes and vitamin C (ascorbic acid) content were measured during five months of storage. The results revealed that apple quality was strongly affected by the temperature fluctuations during frozen storage. The kinetic models were calibrated using apple quality data collected at low and large amplitudes of fluctuations. The temperature dependency was successfully incorporated using an Arrhenius equation that integrates the temperature fluctuations. The kinetic models were validated using apple quality data gathered at a medium amplitude of fluctuation. In addition to a kinetic model, a physical model was applied to predict frost formation.